Pengaruh Kinerja Keuangan, Kompleksitas Operasional, Dan Mekanisme Good Corporate Governance Terhadap Audit Delay Pada Perusahaan Sektor Pertambangan - Ahmad Fadly Fadhilah; Hexana Sri Lastanti (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine financial performance, operational complexity, and good corporate governance mechanisms against audit delay. The sample for this research is 66 mining companies listed on the Indonesia Stock Exchange (BEI) from 2020 to 2022. The data in this research was obtained from secondary data originating from the company's financial reports and annual reports. The analytical method used in this research is multiple linear regression analysis. The results of this research test show that Profitability, Leverage, Operational Complexity, Audit Committee, and Institutional Ownership have no effect on Audit Delay. Meanwhile, the Board of Commissioners has a positive influence on Audit Delay.